THE EFFECT OF SERVICE QUALITY AND CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON CUSTOMER LOYALTY - Farida, Nur; Jannah, Anisa Virdatul (UTSAHA: Journal of Entrepreneurship, 2022)
This study aims to examine and prove the effect of Service Quality and Customer Relationship Management (CRM) on Customer Loyalty at Notary and Land Deed Making Officer (PPAT) A in Lamongan. This study uses a quantitative approach with multiple linear regression analysis. The number of samples taken is 102 respondents and data collection is implemented by questionnaires to obtain the data. The results of this study are that Service Quality and Customer Relationship Management simultaneously affect the customer loyalty at the Notary and Land Deed Making Officer (PPAT) A in Lamongan. The service quality and customer relationship management simultaneously have the significant influence on customer loyalty, and this is verified by the value of Fcount is bigger than the value of Ftable, namely Fcount (29.387) > Ftable (3.12). The customer relationship management partially has a positive effect on customer loyalty and service quality variable partially has a negative effect on customer loyalty.